THE PRESENT STATUS OF THE PUBLIC ACCOUNTING PROFESSION IN JAPAN. - Murase, Gen (The Accounting Review, 1962)
Abstract This article examines the present status of the public accounting profession in Japan. At present there are four kinds of professional accountants in Japan: certified public accountant (CPA), assistant CPA, Foreign CPA and registered CPA. According to the CPA law those who are successful candidates for the CPA Intermediate Examinations are authorized to practice public accounting under the title of Assistant CPA, however they cannot perform the statutory audit under the Securities Exchange Law. Those who have met requirements in foreign countries corresponding to Japanese CPA qualifications and have a sufficient knowledge of Japanese laws and ordinances concerning accounting may practice the profession if their qualifications have been approved by the Japanese Minister of Finance. Such persons must use the title of "Foreign CPA." The agency authorized to control the activities of professional accountants is the Financial Bureau of the Ministry of Finance which registers all practicing accountants.